Experimental study of standing and walking at work — What is compatible with physiological characteristics and human needs?; Experimentelle Studie zum Stehen und Gehen bei der Arbeit – Was ist kompatibel mit physiologischen Eigengesetzlichkeiten und menschlichen Bedürfnissen? - Lisa Rücker; Johannes Brombach; Klaus Bengler (Zeitschrift für Arbeitswissenschaft, 2021)
An experimental study with two scenarios S1 and S2 was conducted, in which the standing and walking proportions as well as movement dynamics were varied. Eleven participants have taken part in the study for 2.5 h each (cycle time: 90 s). By means of surface electromyography, the static and dynamic components of muscle strain as well as the muscle fatigue were recorded and compared with the results of water plethysmography and a~structured subjective rating survey. The results of the EMG study showed significantly higher dynamic components of the EA at S2 compared to S1, while the static components for the same activities did not show any significant difference, as expected. S1 and S2 always led to an increase in volume of the lower leg. Standing with less walking (S1) resulted in a~significantly higher increase than standing with a~higher proportion of walking and stronger dynamic movements (S2). In scenario S2, compared to scenario S1, the participants reported weaker subjective complaints which were also reported later in time. The results on muscular fatigue indicated only partially significant differences between S1 and S2. The results make clear that the dynamics of movement are a~decisive criterion for assessing standing activities. Practical Relevance: To relieve strain during standing work, "real" walking movement must be integrated into the workflow. It could be shown that only a~small step to the side or a~few "shuffling" steps are not sufficient. In contrast, it is compatible with human physiological characteristics to make correct steps and dynamically activate the leg muscles.
Keywords: 650; Water plethysmography; Surface electromyography; Subjective complaints; Static/dynamic muscle strain; Wasserplethysmographie; Oberflächen-Elektromyographie; Subjektive Beschwerden; Statische/dynamische Muskelbeanspruchung